2000
DOI: 10.1021/ic000263u
|View full text |Cite
|
Sign up to set email alerts
|

Bridged Silver(I) Complexes of the Polycyclic Aromatic Compounds Tetraphenylethylene and 1,1,4,4-Tetraphenyl-1,3-butadiene

Abstract: For the purpose of investigating the coordination behavior of the sterically congested alkenes and exploring the possibility of cofacial complexation in the polycyclic aromatic system for formation of extended polymeric networks, tetraphenylethylene (tphe) and 1,1,4,4-tetraphenyl-1,3-butadiene (tphb) have been studied with regard to their complexation with a silver(I) ion. The crystal structures of [Ag(tphe)(ClO4)(p-xylene)], [Ag2(tphe)(ClO4)2], [Ag4(tphe)(CF3SO3)4], [Ag2(tphb)(ClO4)2], and [Ag2(tphb)(CF3SO3)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 36 publications
2
35
1
Order By: Relevance
“…These compounds are complexes of [Ag][A] (e.g. : A = BF 4 , ClO 4 , SO 3 CF 3 ) with chelating ligands such as 1,5-hexadiene, [28] norbornadiene, [22] 1,4,7-cyclononatriene, [23] 1,3,5,7-cyclooctatetraene (and derivatives), [20,24,25,50,51] bullvalene, [26] tetraphenylethene, -butadiene [19] and other substituted alkenes. [17,18,21,27,52] However, these olefins are solids or liquids and, therefore, the entropic contribution to dissociation (and thus decomposition) is much smaller than that for the lightest parent olefin C 2 H 4 .…”
Section: -C H 4 ) 3 ]mentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds are complexes of [Ag][A] (e.g. : A = BF 4 , ClO 4 , SO 3 CF 3 ) with chelating ligands such as 1,5-hexadiene, [28] norbornadiene, [22] 1,4,7-cyclononatriene, [23] 1,3,5,7-cyclooctatetraene (and derivatives), [20,24,25,50,51] bullvalene, [26] tetraphenylethene, -butadiene [19] and other substituted alkenes. [17,18,21,27,52] However, these olefins are solids or liquids and, therefore, the entropic contribution to dissociation (and thus decomposition) is much smaller than that for the lightest parent olefin C 2 H 4 .…”
Section: -C H 4 ) 3 ]mentioning
confidence: 99%
“…Solution NMR spectroscopy: Signals of the 1 H, 13 C, 19 F, and 27 Al NMR spectra of 1 to 5 in CD 2 Cl 2 that can be assigned to the anionic parts [A] are similar to other salts with the same anions [59] and are therefore not discussed in detail.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The starting molecular geometry was extracted from ref. [26] followed by geometry optimization performed using the restricted Hartree-Fock Austin model 1 (AM1) method. The optical transitions were calculated with ZINDO/S, which uses theoretically based intermediate neglect of differential overlap (INDO) parameterized to reproduce UV/VIS spectroscopic transitions with a configuration interaction (CI) including all singly excited configurations, with 10 eV limit between the occupied and unoccupied orbitals.…”
Section: Methodsmentioning
confidence: 99%
“…Two of them have monoclinic crystallographic structures and have been directly observed during our study, while a triclinic polymorph is reported in the literature. [26] The unit cell of one of the monoclinic polymorphs is reported by Baba et al [27] Here, we focus on the optical properties of the other monoclinic polymorph, whose crystallographic structure, to our knowledge, is not reported in the literature. The space group of this new polymorph is P2 1 /c.…”
Section: Polarized Absorptionmentioning
confidence: 98%